Extended Spectrum β-Lactamase (ESBL) Producing Escherichia coli in Pigs and Pork Meat in the European Union - Ieva Bergšpica; Georgia Kaprou; Elena A. Alexa; Miguel Prieto; Avelino Alvarez-Ordóñez (Antibiotics, 2020)
The aim of this article is to review the fast and worldwide distribution of ESBL enzymes and to describe the role of the pork production chain as a reservoir and transmission route of ESBL-producing Escherichia coli and ESBLs in the European Union (EU). The use of β-lactam antibiotics in swine production and the prevalence of ESBL producing E. coli in fattening pigs and pork meat across Europe is analyzed. Overall, an increasing trend in the prevalence of presumptive ESBL producing E. coli in fattening pigs in the EU has been observed in the last decade, although with major differences among countries, linked to different approaches in the use of antimicrobials in pork production within the EU. Moreover, the various dissemination pathways of these bacteria along the pork production chain are described, along with factors at farm and slaughterhouse level influencing the risk of introducing or spreading ESBL producing bacteria throughout the food chain.